Modeling of torrefaction of small biomass particles. Issue 2 (17th February 2020) - Kamila, Biswajit; Sadhukhan, Anup Kumar; Gupta, Parthapratim; Basu, Prabir; Acharya, Bishnu
ABSTRACT: A simple single-step kinetic model consisting of two parallel reactions is proposed for torrefaction of small biomass particles. The model is validated against experimental data on torrefaction of poplar wood fines. Comparison of experimental data and model prediction shows that the results predicted by the proposed simplified model are as accurate as those from the models of Di Blasi and Lanzetta (1997) and Rousset et al. (2006) which involve larger numbers of model parameters – eight and sixteen, respectively – compared to four in the proposed model. This makes it suitable for incorporation into the overall reactor model. At 493 and 553 K, the relative mean errors are found to be 0.056, 0.080, 0.051 and 0.050, 0.100, 0.048 for the proposed model, Rousset et al.'s (2006) model and Blasi and Lanzetta's (1997) model, respectively. The effect of particle size, temperature and residence time on torrefaction of biomass is investigated. A transformation of rate-controlling regime from kinetic to heat transfer is identified with an increase in particle size and temperature. Sensitivity analysis shows that the dimensionless groups such as pyrolysis number, dimensionless heat of reaction and dimensionless activation energy have significant influence on the particle temperature and torrefaction behaviour.